Gender difference in functional activity of 4-months-old infants during sleep: A functional near-infrared spectroscopy study - Wang, Kai; Ji, Xiang; Li, Ting (Frontiers in Psychiatry, 2023)
Sex differences emerge early in infancy, and some of these sex differences can be detected by testing the function localization of the human cerebrum. This study uses an open access dataset of task-free hemodynamic activity in 4-month-old infants during sleep by functional near-infrared spectroscopy (fNIRS), to identify some difference between male and female infants. The results of this study showed that female and male infants had different Power Spectral Density (PSD) for oxyhemoglobin (HbO) and deoxyhemoglobin (HbR) at rest, showing stronger differences at frontoparietal network, somatomotor network and ventral attention network. This may be due to the differences in the timing or extent of development of those networks. These differences will provide some assistance in future studies of the early education of male and female infants.